Growth and proximate composition of tropical marine Chaetoceros calcitrans and Nannochloropsis oculata cultured outdoors and under laboratory conditions - Banerjee, Sanjoy; Hew, Wei Ee; Khatoon, Helena; Mohamed Din, Mohamed Shariff; Md. Yusoff, Fatimah (Academic Journals, 2011)
The growth and proximate composition of two marine microalgae, Chaetoceros calcitrans and Nannochloropsis oculata, cultured outdoors under shade (24 to 36°C, 140 μmol/m 2/s) and laboratory conditions (environmental chamber, 23°C for C. calcitrans and 20°C for N. oculata, 150 μmol/m 2/s) were compared. Outdoor cultures of both C. calcitrans and N. oculata had significantly higher (p < 0.05) biomass, cell count, optical density and specific growth rate compared to the cultures grown under laboratory conditions. Lipid content was significantly higher in C. calcitrans grown outdoors, whereas, protein and carbohydrate composition did not show any significant differences (p > 0.05) between the outdoor and laboratory cultures. In the case of N. oculata, no significant differences (p > 0.05) were found in protein and lipid composition, but carbohydrate was significantly higher (p < 0.05) in the outdoor culture. In addition, the results showed that both C. calcitrans and N. oculata cultures grew faster outdoors, producing more biomass within a shorter period of time. This study illustrated that outdoor culture of microalgae was viable despite the fluctuating environmental conditions.